2011
DOI: 10.1182/blood-2010-08-303800
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between bone, hemopoietic stem cells, and vasculature

Abstract: A large body of evidence suggests hemopoietic stem cells (HSCs) exist in an endosteal niche close to bone, whereas others suggest that the HSC niche is intimately associated with vasculature. In this study, we show that transplanted hemopoietic stem and progenitor cells (HSPCs) home preferentially to the trabecular-rich metaphysis of the femurs in nonablated mice at all time points from 15 minutes to 15 hours after transplantation. Within this region, they exist in an endosteal niche in close association with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
99
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 48 publications
8
99
0
4
Order By: Relevance
“…Previously, hyaluronan had been shown to be highly haematologica | 2016; 101(1) expressed at the endosteal BM surface as well as acting as a negative regulator of HSC proliferation. 18,48 This could also explain why endosteal HSC have significantly higher CD44 expression compared to centrally isolated HSC.…”
Section: Cd44mentioning
confidence: 85%
See 2 more Smart Citations
“…Previously, hyaluronan had been shown to be highly haematologica | 2016; 101(1) expressed at the endosteal BM surface as well as acting as a negative regulator of HSC proliferation. 18,48 This could also explain why endosteal HSC have significantly higher CD44 expression compared to centrally isolated HSC.…”
Section: Cd44mentioning
confidence: 85%
“…20 We have previously demonstrated that HSC isolated from the endosteal region home to BM better than their central counterparts as well as preferentially home back to the endosteal region, 38 and that hyaluronan is highly expressed in the endosteal BM region compared to central BM. 18,48 Therefore, without CD44, HSC and progenitors may have impaired interactions with their microenvironment during the homing process. Furthermore, hyaluronan has been shown to act as a chemoattractant via CD44 63 and we did not find any differences in the expression of HAS3, critical in the generation of hyaluronan, in CD44 -/-mouse BM (data not shown).…”
Section: Cd44mentioning
confidence: 99%
See 1 more Smart Citation
“…HSPCs have been imaged for short periods of time through coverslips placed over excised, fractured femurs [11] , however the impact of this harsh preparation of the tissue on HSPCs is not clear and the technique was used uniquely to obtain single time point observations. Fixed bones have been sectioned into serial sections, stained, and the obtained images reconstructed into a 3D model, providing excellent 3D resolution, especially when vascular casts are used [17] , and recently Laser Scanning Cytometry (LaSC) has been used to obtain quantitative measures about HSPCs in situ, highlighted by immunostaining [18] but are unable to provide any temporal information about the cells behavior. The techniques described in this new technique provide a combination of good resolution in 3D, sufficient temporal sampling for monitoring cells in 4D and they are relatively non-invasive, therefore offering an ideal approach to achieve long-term monitoring of HSPCs interacting with the bone marrow microenvironment.…”
Section: Limitationsmentioning
confidence: 99%
“…This process is highly regulated by a dynamic interaction of chemokines and adhesion molecules to ensure a purposive homing and engraftment. 22 We recently demonstrated that more than 80% of transplanted murine HSC home to the BM within 5 h. 23 As our clinical data indicate that early engraftment of neutrophils is significantly delayed in MF patients, we used the clearance of the HSC from the PB as a surrogate marker for the homing of HSC. We show that more than 75% of the transplanted CD34 + cells exited the PB within 40 min and the number of circulating CD34 + cells after 22 h was the same as that prior to transplantation.…”
mentioning
confidence: 99%